MI5, the Cold War, and the rule of law - Ewing, K. D. (Oxford scholarship online, 2020)
This innovative study of the status, powers, and activities of MI5 during the Cold War contends that MI5 was subject neither to effective political nor legal scrutiny, and examines the operations of the Security Service for civil liberties, and the contemporary relevance of Cold War practices.